Reduced Growth, Altered Gut Microbiome and Metabolite Profile, and Increased Chronic Kidney Disease Risk in Young Pigs Consuming a Diet Containing Highly Resistant Protein - Murray, Margaret; Coughlan, Melinda T.; Gibbon, Anne; Kumar, Vinod; Marques, Francine Z.; Selby-Pham, Sophie; Snelson, Matthew; Tsyganov, Kirill; Williamson, Gary; Woodruff, Trent M.; Wu, Tong; Bennett, Louise E. (Frontiers in Nutrition, 2022)
High-heat processed foods contain proteins that are partially resistant to enzymatic digestion and pass through to the colon. The fermentation of resistant proteins by gut microbes produces products that may contribute to chronic disease risk. This pilot study examined effects of a resistant protein diet on growth, faecal microbiome, protein fermentation metabolites and biomarkers of health status in pigs as a model of human digestion and metabolism. Weanling pigs were fed standard or resistant protein diets for 4 weeks. The resistant protein, approximately half as digestible as the standard protein, was designed to enter the colon for microbial fermentation. Faecal and blood samples were collected to assess the microbiome and circulating metabolites and biomarkers. The resistant protein diet group consumed less feed and grew to ~50% of the body mass of the standard diet group. The diets had unique effects on the faecal microbiome, as demonstrated by clustering in the principal coordinate analysis. There were 121 taxa that were significantly different between groups (adjusted-p<0.05). Compared with control, plasma tri-methylamine-N-oxide, homocysteine, neopterin and tyrosine were elevated and plasma acetic acid was lowered following the resistant protein diet (all p<0.05). Compared with control, estimated glomerular filtration rate (p<0.01) and liver function marker aspartate aminotransferase (p<0.05) were also lower following the resistant protein diet. A resistant protein diet shifted the composition of the faecal microbiome. Microbial fermentation of resistant protein affected levels of circulating metabolites and biomarkers of health status towards a profile indicative of increased inflammation and risk of chronic kidney disease.